2015
DOI: 10.1016/j.redox.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

“Twin peaks”: Searching for 4-hydroxynonenal urinary metabolites after oral administration in rats

Abstract: 4-Hydroxynonenal (HNE) is a cytotoxic and genotoxic lipid oxidation secondary product which is formed endogenously upon peroxidation of cellular n-6 fatty acids.However, it can also be formed in food or during digestion, upon peroxidation of dietary lipids. Several studies have evidenced that we are exposed through food to significant concentrations of HNE that could pose a toxicological concern. It is then of importance to known how HNE is metabolized after oral administration. Although its metabolism has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…It accumulates in the body and is difficult to remove (Esterbauer, Schaur, & Zollner, 1991). Keller, Baradat, Jouanin, Debrauwer, and Guéraud (2015) used radiolabeled HNE to track the HNE metabolism in rats after oral administration. It was reported that HNE originating from the diet was metabolized in vivo and incorporated into the cecum, liver, small intestine, colon, kidneys, stomach, and also into the brain and heart.…”
Section: Introductionmentioning
confidence: 99%
“…It accumulates in the body and is difficult to remove (Esterbauer, Schaur, & Zollner, 1991). Keller, Baradat, Jouanin, Debrauwer, and Guéraud (2015) used radiolabeled HNE to track the HNE metabolism in rats after oral administration. It was reported that HNE originating from the diet was metabolized in vivo and incorporated into the cecum, liver, small intestine, colon, kidneys, stomach, and also into the brain and heart.…”
Section: Introductionmentioning
confidence: 99%
“…These products include various lipophilic aldehydes such as alkanals, alkenals, alkadienals and hydroxyalkenals and these compounds are readily absorbed from the diet [10] [11] [12] [13]. One class of aldehydes, the toxic 4-hydroxyalkenals, generated from lipid peroxidation of unsaturated FA are of special importance because of their reactivity to biomolecules [14] [15]. The cytotoxicity of 4-hydroxynonenal (HNE) [16] has been found to be formed from the oxidation of n-6 FA, including linoleic acid [12] [15] [17] which is high in polyunsaturated fatty acids (PUFA).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Esterbauer and colleagues established that such 4-hydroxyalkenals were highly reactive and could bind with most amino acids, and that HNE had been implicated in the etiology of atherosclerosis, diabetes, and neurodegenerative diseases [2]- [4]. In addition to vitamin E deficiency and impaired endogenous antioxidant systems, a diet high in PUFA would be expected to increase total lipid peroxidation within an organism [5]- [9]. Previous research from our laboratory demonstrated that heating methyl linolenate, formed from the omega-3 (n − 3) PUFA α-linolenic acid (ALA, 18:3 n − 3), yielded detectable quantities of HHE [10], but limited human research had documented its production via in vivo lipid peroxidation following n − 3 consumption [11].…”
Section: Introductionmentioning
confidence: 99%